Establishment and Production Costs for Peach Orchards in Florida: Enterprise Budget and Profitability Analysis - Ariel Singerman; Marina Burani Arouca; Mercy A. Olmstead (EDIS)
The article summarizes the establishment and production costs, as well as the potential profitability of a peach orchard in Florida. Our findings show the initial investment required for a peach operation in Florida to be $6,457 per acre; the expense in land preparation and planting alone in year 1 is $2,541 per acre. Variable and fixed costs in years 2 through 15 average $5,680 per acre. As an example of profitability, when using a 10% discount rate, an operation yielding 6,525 (7,254) pounds of marketable fruit per acre during its most productive years obtains a positive NPV when the average price is $2.38 ($2.13) per pound.